Discovery of a new chemical series of BRD4(1) inhibitors using protein-ligand docking and structure-guided design. Issue 14 (15th July 2015) - Duffy, Bryan C.; Liu, Shuang; Martin, Gregory S.; Wang, Ruifang; Hsia, Ming Min; Zhao, He; Guo, Cheng; Ellis, Michael; Quinn, John F.; Kharenko, Olesya A.; Norek, Karen; Gesner, Emily M.; et al.
Graphical abstract